Dreaming in dark times : six exercises in political thought - Sliwinski, Sharon, 1975- (University of Minnesota Press, 2017)
"What do dreams manage to say--or indeed, show--about human experience that is not legible otherwise? Can the disclosure of our dream-life be understood as a form of political avowal? To what does a dream attest? And to whom? Blending psychoanalytic theory with the work of such political thinkers as Hannah Arendt and Michel Foucault, Sharon Sliwinski explores how the disclosure of dream-life represents a special kind of communicative gesture--a form of unconscious thinking that can serve as a potent brand of political intervention and a means for resisting sovereign power. Each chapter centers on a specific dream plucked from the historical record, slowly unwinding the significance of this extraordinary disclosure. From Wilfred Owen and Lee Miller to Frantz Fanon and Nelson Mandela, Sliwinski shows how each of these figures grappled with dream-life as a means to conjure up the courage to speak about dark times. Here dreaming is defined as an integral political exercise--a vehicle for otherwise unthinkable thoughts and a wellspring for the freedom of expression. Dreaming in Dark Times defends the idea that dream-life matters--that attending to this thought-landscape is vital to the life of the individual but also vital to our shared social and political worlds"--